Constituent Power, the Rights of Nature, and Universal Jurisdiction - Colón-Ríos, Joel (McGill Law Journal / Revue de droit de McGill, 2014)
This article provides a justification for the exercise of universal jurisdiction in cases of serious environmental damage. This justification rests in important ways on the theory of constituent power. The theory of constituent power has an intergenerational component that requires the protection of the environmental conditions that allow future generations to engage in constitution-making episodes. This article maintains that, by virtue of the connections between constituent power, the right to self-determination, and state sovereignty, the justification for the exercise of universal jurisdiction for serious environmental damage is at least as compelling as the justification for its exercise with respect to egregious human rights infringements. In those scenarios, courts exercising universal jurisdiction would be acting to protect the ability of present and future peoples to participate in the constitution and reconstitution of the states that make up the international community. Such a jurisdiction would rest on the authority of humanity as a whole rather than on that of any state or people.